2019
DOI: 10.1177/1933719118766266
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Vaginal Administration Contrasts Inflammation and Preterm Delivery in Rats

Abstract: α-Lipoic acid (ALA) is a safe natural molecule involved in the immunomodulation of many physiological processes. Orally administered ALA has been reported to treat several inflammatory pathologies and support pregnancy. Our study aimed at testing ALA vaginal administration in female Wistar rats evaluating its tissue distribution (experiment I), impact on implantation process (experiment II), and effectiveness in contrasting induced preterm birth (experiment III). In experiment I, rats were intravaginally treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Considering the promising antioxidant potential of ALA and its impact in multiple inflammatory conditions, recent evidences have increasingly highlighted its impact in physiological processes, such as pregnancy. Interestingly, Micili et al [90] assessed the impact of ALA vaginal administration in female Wistar rats, namely testing its tissue distribution, impact on implantation process and effectiveness in contrasting induced preterm birth. Curiously, the authors found that vaginal ALA is well-absorbed and distributed, without affecting the implantation process and was even able to significantly revert mifepristone plus prostaglandin E2 effects, thus, delaying the delivery timing and decreasing the synthesis of mRNA and pro-inflammatory cytokines release [90].…”
Section: Preclinical Actability Of α-Lipoic Acidmentioning
confidence: 99%
“…Considering the promising antioxidant potential of ALA and its impact in multiple inflammatory conditions, recent evidences have increasingly highlighted its impact in physiological processes, such as pregnancy. Interestingly, Micili et al [90] assessed the impact of ALA vaginal administration in female Wistar rats, namely testing its tissue distribution, impact on implantation process and effectiveness in contrasting induced preterm birth. Curiously, the authors found that vaginal ALA is well-absorbed and distributed, without affecting the implantation process and was even able to significantly revert mifepristone plus prostaglandin E2 effects, thus, delaying the delivery timing and decreasing the synthesis of mRNA and pro-inflammatory cytokines release [90].…”
Section: Preclinical Actability Of α-Lipoic Acidmentioning
confidence: 99%
“…87 Further, in a recent experimental study, ALA proved to contrast preterm delivery induced by mifepristone and PGE2 in rats. 44 Further, fetal tissue is more vulnerable to oxidative damage due to rapid cell proliferation. 81 Ara-C is known to cause fetotoxicity which includes fetal resorption, still birth, weight reduction, and various external and internal developmental anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ALA in pregnancy found to be very promising in improving pregnancy outcomes and have no adverse effects on pregnancy. 40,44,45 Further, ALA protective role in ameliorating the pregnancy-related disorders like subchorionic hematomas, miscarriage, and preterm delivery 44,[85][86][87] or chemical-or disease-induced developmental toxicity has been demonstrated in several studies. 47,84,94 Coadministration of ALA showed a significant reduction in OS markers, the incidence of fetal resorption, death, hematoma and increase in weight reduction, crown-to-rump length as compared to group received Ara-C only and is clearly indicating its protective effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…follicle development in vitro is improved by the reduction of reactive oxygen species (ROS) levels and the increase of antioxidant capacity in follicles [11]. Moreover, it is associated with the prevention of miscarriage [12,13] and the treatment of endometriosis and vestibulodynia [14,15]. ALA treatment has shown to be effective in many POI animal models, such as in cyclophosphamideinduced and 4-vinyl cyclohexene dioxide induced POI rats [16,17].…”
Section: Introductionmentioning
confidence: 99%